Character Is Caught, Not Taught: Narrative Inquiry into How Santri Experience Moral Formation, Kiai Authority, and Character Education in Indonesian Pesantren - Husna Nashihin; La Hadisi; Sugito Sugito; Aris Munandar; Zulkifli Musthan; Anzar Aquil (International Journal of Educational Narratives, 2026)
Background. The study is motivated by the increasing attention to character education as a response to moral crises, social transformation, and challenges of Islamic education in the digital era. Purpose. This study aims to analyze the development of scientific publications on character education in Islamic boarding schools during the 2016–2025 period through a bibliometric approach. Method. The research employed a bibliometric method using data obtained from the Scopus database. Data collection was conducted using keywords related to character education, moral education, pesantren, Islamic boarding school, and Islamic education. After the screening process based on publication year, document type, and language, 111 documents were selected and analyzed using VOSviewer software. Results. The findings reveal that publications on character education in pesantren increased significantly after 2020 and reached their peak during 2024–2025. Research themes evolved from normative approaches toward more multidisciplinary issues such as religious moderation, anti-bullying, digital transformation, and entrepreneurship. Indonesia emerged as the dominant contributor to publications in this field, accounting for approximately 90% of the analyzed documents. Conclusion. This study contributes by providing a scientific mapping of research trends, collaboration networks, and future research opportunities related to character education in Islamic boarding schools based on a predominantly Indonesian research landscape indexed in Scopus. The findings confirm that pesantren-based character education holds a strategic role in the development of contemporary Islamic education while highlighting opportunities for broader international collaboration and comparative research.